2015
DOI: 10.5507/bp.2013.007
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene improves the distorted ratio between AA/DHA in the seminal plasma of infertile males and increases the likelihood of successful pregnancy

Abstract: Aims. Male infertility has been associated with imbalance in the polyunsaturated fatty acids arachidonic acid/docosahexaenoic acid (AA/DHA) ratio. This study aimed to assess whether use of the potent antioxidant, lycopene, would affect this imbalance in seminal plasma and to test whether modulation of the AA/DHA ratio correlates with male fertility. Methods. The study included 44 males from infertile couples who were treated with lycopene for three months before scheduled IVF treatment. The control group was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
8
1
1
Order By: Relevance
“…Various earlier studies have reported a significant decrease in LPO following LYC supplementation (Goyal et al 2006;Aly et al 2012;Sarkar et al 2012;Filipcikova et al 2015). Our findings are, however, inconsistent with Zribi et al (2011) who reported that although oxidative stress was linked to DNA damage, no correlations were recorded between nuclear alterations and MDA levels.…”
Section: Discussioncontrasting
confidence: 57%
“…Various earlier studies have reported a significant decrease in LPO following LYC supplementation (Goyal et al 2006;Aly et al 2012;Sarkar et al 2012;Filipcikova et al 2015). Our findings are, however, inconsistent with Zribi et al (2011) who reported that although oxidative stress was linked to DNA damage, no correlations were recorded between nuclear alterations and MDA levels.…”
Section: Discussioncontrasting
confidence: 57%
“…Improvement in semen quality reflects the efficacy of the antioxidant treatment, hence it is not surprising that evaluation of semen parameters after antioxidant therapy is the main outcome reported in 93% of the top-cited original articles. However, a real positive effect of antioxidant therapy on semen quality is still under debate as studies report contradictory results including improvement [ 59 60 61 ] or no changes [ 62 63 64 ]. This discrepancy may be due to incorrect patient selection or a different response to the therapy due to different pathophysiological background of the patients included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials also focused on the antioxidant properties of LYC in the context of oxidative stress-compromised male reproductive function. Filipcikova et al [ 113 ] observed a significant decrease of MDA production in the seminal plasma of infertile men consuming 10 mg of highly purified LYC from tomato puree and emphasized on the efficacy of LYC in stabilizing the levels of polyunsaturated fatty acids in the sperm membranes. Taş et al [ 114 ] speculated that this LPO-preventing potential lies in the ability of LYC to become entrapped in the hydrophobic core of membranous constituents in spermatozoa.…”
Section: Lycopenementioning
confidence: 99%